Field notes contributed by Hank Zaletel, spring 1988 - Zaletel, Hanket al (1988)
List of birds and locations contributed by Hank Zaletel. The field notes include a detailed description of the Peregrine Falcon. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1988. Epson - sheet feed/flatbed